HGG-17. Novel Fusion in Congenital Brainstem Diffuse High-Grade Glioma. (3rd June 2022) - Norris, Gregory; Donson, Andrew; Milgrom, Sarah; Gaskell, Alisa; Willard, Nicholas; Foreman, Nicholas; Gilani, Ahmed; Dahl, Nathan
Abstract: BACKGROUND: Infant-type hemispheric glioma, previously termed infantile glioblastoma multiforme, is a rare infantile neoplasm with improved survival and distinct molecular features when compared to other pediatric and adult-type high-grade glioma. Infant-type high-grade gliomas are typically located in the cerebral hemispheres and are characterized by ALK, ROS1, MET, and NTRK fusions. Typical brainstem gliomas (diffuse midline glioma, H3 K27-altered or diffuse intrinsic pontine glioma) are comparatively rare in this age group. As a result, the biology of brainstem congenital high-grade gliomas is poorly described. RESULTS: A 3 month old female who initially presented with failure to thrive had an apneic event and was found to have an infiltrative mass in the medulla with expansion into the pons and cervical spine on magnetic resonance imaging. She underwent surgical biopsy with pathology revealing diffuse high-grade glioma, WHO grade 4. Next generation sequencing showed no alterations to H3F3A, IDH, or fusions involving BRAF, ALK, ROS1, MET, or NTRK. Whole-transcriptome sequencing revealed a novel fusion of PDGFRB:APOBEC3C. She received chemotherapy with 2 cycles of carboplatin/etoposide and 2 cycles of carboplatin/etoposide/imatinib before having disease progression. She then underwent palliative radiation (35 Gy in 10 fractions) with near complete regression of her disease. Surprisingly, our patient has not had any progression of disease or new lesions now two years from her last therapy. CONCLUSION: Congenital high-grade glioma is a rare, unique entity that greatly differs from its adult and childhood counterparts. Here, we discuss a previously-unreported fusion of PDGFB:APOBEC3C in a patient with congenital brainstem diffuse high-grade glioma with a favorable clinical course. This highlights the importance of routine molecular characterization, both to better understand the complex biology of this rare disease and to guide prognosis and clinical decision making for individual patients and families.